MACULAR VASCULAR DENSITY ANALYSIS USING ADOBE PHOTOSHOP SOFTWARE IN DIABETIC EYES: OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY STUDY - Shah, Syed Nasir Ali; Luo, Yan; Idrees, Muhammad; Farooq, Umer; Pan, Jian ying; Yan, Lu RU; Jin, Lu; khan, Muhammad Usman; Saeed, Tariq Muhammad; Ahmad, Zara (Journal of Ayub Medical College Abbottabad, 2021)
Background: Optical Coherence Tomography Angiography (OCTA) is dye less microvascular visualizing technique. In study we binaries OCTA images of macular vessels in healthy and diabetic subjects without macular oedema using Adobe Photoshop CS3 extended version. Methods: Prospective, single centered, observational study total of 58 eyes of 108 Diabetic Retinopathy (DR) subjects and 20 eyes of 40 normal subjects with mean age of 58.3±10.5 range (40-82) were included in our study. Ten eyes with Non-Diabetic Retinopathy (NDR), twenty-nine eyes with Non-Proliferative Diabetic Retinopathy (NPDR) (mild-10, moderate-7 and severe-12) and nineteen eyes with Proliferative Diabetic Retinopathy (PDR)are studied with images obtained using OCTA between September 2016 to June 2017. Scan area of 6Ã—6 mm was selected to find morphological changes in the superficial retinal layers and deep retinal layers. Captured OCTA images were binarized using automated thresholding algorithm. Macular Vessel Density (MVD) (%) and Foveal Avascular Zone area (mm2) measured for superficial and deep retinal vessel arcade. For comparison, analysis of variance and Kruskal-Wallis test are applied. Results: Diabetic eyes were grouped according to their severity level. MVD and FAZ are compared in all groups. Results are significantly lower in all groups except in controls and NDR. Significant decrease is observed in vascular density of most layers with progress in retinopathy. Conclusion: Adobe Photoshop CS3 extended version is an excellent tool for image binarization. Calculating FAZ area and MVD using OCTA images agreed closely with clinical grading system. Application of this method can be helpful in monitoring disease progression.